2013
DOI: 10.1001/jama.2013.8278
|View full text |Cite|
|
Sign up to set email alerts
|

Views of US Physicians About Controlling Health Care Costs

Abstract: Importance Physicians' views about health care costs are germane to pending policy reforms. Objective To assess physicians' attitudes toward and perceived role in addressing health care costs. Design, Setting, and Participants A cross-sectional survey mailed in 2012 to 3897 US physicians randomly selected from the AMA Masterfile. Main Outcomes and Measures Enthusiasm for 17 cost-containment strategies and agreement with an 11-measure cost-consciousness scale. Results A total of 2556 physicians responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
198
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(211 citation statements)
references
References 15 publications
9
198
3
1
Order By: Relevance
“…[1][2][3][4][5]30 Despite the current nationwide effort to improve value in health care, viewpoints of frontline practicing clinicians on how to achieve better health and decreased costs remain largely unknown. 31 Most physicians agree that they should take a greater role in reducing unnecessary tests, 32 but little is known about the extent to which the typical emergency physician (EP) believes unnecessary diagnostic testing occurs in his or her practice setting or what solutions, if any, she or he feels would help mitigate this practice. Such information is crucial to achieving high-value care and may be especially helpful in light of the upcoming 2015 Academic Emergency Medicine (AEM) consensus conference on diagnostic imaging.…”
mentioning
confidence: 99%
“…[1][2][3][4][5]30 Despite the current nationwide effort to improve value in health care, viewpoints of frontline practicing clinicians on how to achieve better health and decreased costs remain largely unknown. 31 Most physicians agree that they should take a greater role in reducing unnecessary tests, 32 but little is known about the extent to which the typical emergency physician (EP) believes unnecessary diagnostic testing occurs in his or her practice setting or what solutions, if any, she or he feels would help mitigate this practice. Such information is crucial to achieving high-value care and may be especially helpful in light of the upcoming 2015 Academic Emergency Medicine (AEM) consensus conference on diagnostic imaging.…”
mentioning
confidence: 99%
“…Previous research has clearly demonstrated that physicians' perceive a tension between their responsibility to practice cost-consciously and their ability to serve their patients' best interests, 13,[17][18][19] which often manifests in a desire to fulfill their patients' expectations. 5,[14][15][16] Our data suggest that physicians do consider resources in the daily care of patients, but some may be more adept at balancing this tension than others.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent survey, 85 % of physicians agreed that "trying to contain cost is the responsibility of every physician;" however, more than three-quarters also agreed they "should be solely devoted to their individual patients' best interests, even if that is expensive." 13 Cost-conscious practice is particularly challenging when physicians are faced with patient expectations or request for medical services that may be unnecessary. Previous studies have demonstrated that patient requests influence physician behavior, even after controlling for predisposing factors and the underlying necessity of the request.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that this was a small, single-institution sample of medical students near the beginning of their clinical training, students were able to identify many common practices, echoed by residents [ 2 ] and attendings [ 3 ], that were not consistent with the practice of high-value care. However, the possibility for availability bias is pronounced, as the themes outlined by students closely mirrored those taught in the required online module.…”
mentioning
confidence: 94%